Impact of microbial biotransformation on Zygophyllum decumbens delile through comparative metabolic insights and evaluation of antihyperglycemic and antimicrobial activities - Alaadin E. El-Haddad; Soad M. Abd El-Khalik; Lina J. M. Abdel-Hafez; Jaky T. Zaki; Nagwan M. Gabr (Scientific Reports)
Abstract Zygophyllum is known to be used traditionally in the management of several medical conditions, including diabetes, infections, and hypertension. This study aims to monitor the effect of microbial biotransformation on both antihyperglycemic and antimicrobial activities of Zygophyllum decumbens Delile using Aspergillus niger. The metabolic profile before and after biotransformation of the ethyl acetate extract was compared using HPLC-ESI-TOF-MS/MS. Pancreatic lipase, α-amylase, and α-glucosidase in vitro inhibition assays and agar diffusion method were used to evaluate the antihyperglycemic and antimicrobial activities, respectively. Eighty-six metabolites, mainly flavonoids and phenolic acids, with a few miscellaneous metabolites, were tentatively identified in both tested extracts. A 36% potentiation in antihyperglycemic activity was observed following microbial biotransformation. Regarding antimicrobial activity, the minimum inhibitory concentration (MIC) against both E. coli and P. aeruginosa decreased from 0.62 to 0.31 mg/ml, representing a nearly 50% reduction. It was noticed that microbial biotransformation altered 27 of the identified metabolites, which may contribute to the enhanced biological activities detected. The study depicts the first report of metabolic profiles and biological differences of Z. decumbens before and after biotransformation. It also validates the traditional use of Z. decumbens for hyperglycemia and its potential as a natural antimicrobial source.